2020
DOI: 10.18502/jfqhc.7.3.4144
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Aflatoxins in Maize-Groundnuts Complemen-tary Foods Consumed by Ghanaian Infants

Abstract: Background: Complementary foods are given to infants when breast milk alone becomes insufficient in meeting their nutritional needs. The major objective of this study was to assess the prevalence of Aflatoxins (AFs) in Weanimix complementary foods purchased from shops in Accra (Ghana), and to estimate risk of liver cancer development in infants.  Methods: In total, 32 samples of Weanimix were purchased from shops in Accra, an urban centre and analyzed for AFs by Reverse-Phase High Performance Liquid Chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The Estimated Daily Intakes (EDI) of total aflatoxins in the maize samples recorded by Kortei et al 2 were 109.7, 58.8, 33.08, and 25.2 μg/kg bw/day for infants, children, adolescents, and adults with Margin of Exposure (MOE) values of 4.73, 8.79, 15.63 and 20.51 respectively. Exposure assessment carried out by Omari and Anyebuno 95 showed that the minimum and maximum daily AFS exposures were 0.044 and 2.805 µg/kg bw/day, respectively for weanimix (infant complementary food prepared from maize) for rural households; these rates for complementary food purchased from urban shops were 0.014 and 0.55 µg/kg bw/day, respectively. The chances of liver cancer development would increase to 0.6 per year if infants were fed with complementary food prepared in rural households with a minimum AF level of 7.9 µg/kg.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…The Estimated Daily Intakes (EDI) of total aflatoxins in the maize samples recorded by Kortei et al 2 were 109.7, 58.8, 33.08, and 25.2 μg/kg bw/day for infants, children, adolescents, and adults with Margin of Exposure (MOE) values of 4.73, 8.79, 15.63 and 20.51 respectively. Exposure assessment carried out by Omari and Anyebuno 95 showed that the minimum and maximum daily AFS exposures were 0.044 and 2.805 µg/kg bw/day, respectively for weanimix (infant complementary food prepared from maize) for rural households; these rates for complementary food purchased from urban shops were 0.014 and 0.55 µg/kg bw/day, respectively. The chances of liver cancer development would increase to 0.6 per year if infants were fed with complementary food prepared in rural households with a minimum AF level of 7.9 µg/kg.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Previous work by some researchers (Kumi et al, 2014;Blankson and Mill-Robertson 2016;Opoku et al, 2018;Omari and Anyebuno 2020;Tuffour and Steele-Dadzie, 2019) in Ghana, revealed some evidence of the incidence of acute aflatoxicosis in children presumably via infant complementary foods. This troubling and uncomfortable situation stems from the overreliance and seemingly inevitable use of the two most frequently fungus-contaminated foodstuffs, maize, and groundnuts as ingredients for the preparation of complementary foods (porridges) for infants, children, and toddlers (Achaglinkame et al 2017;Kortei et al 2021a).…”
Section: Introductionmentioning
confidence: 96%
“… Food products Mycotoxin detected Fungus References Maize grains (whole) Aflatoxins Aspergillus flavus 57 59 Ochratoxins Aspergillus carbonarius, Penicillium verucosum Maize powder Aflatoxins A. flavus 12 , 60 , 61 Fermented maize Fumonisins Fusarium verticillioides 62 – 64 Aflatoxins A. flavus Kenkey Aflatoxins A. flavus 60 Ice kenkey Aflatoxins A . flavus 65 Weanimix cereals Fumonisins Fusarium verticillioides 66 Aflatoxin A. flavus 67 Maize-groundnut mix Aflatoxins A. flavus 68 Dry cassava products Aflatoxins A. flavus 47 Kokonte Aflatoxins A. flavus 47 ...…”
Section: Introductionmentioning
confidence: 99%